2001
DOI: 10.1557/jmr.2001.0416
|View full text |Cite
|
Sign up to set email alerts
|

Observations of structural order in ion-implanted amorphous silicon

Abstract: Medium-range order in ion-implanted amorphous silicon has been observed using fluctuation electron microscopy. In fluctuation electron microscopy, variance of dark-field image intensity contains the information of high-order atomic correlations, primarily in medium-range order length scale (1–3 nm). Thermal annealing greatly reduces the order and leaves a random network. It appears that the free energy change previously observed on relaxation may therefore be associated with randomization of the network. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Paracrystalline models do indeed depict more dihedral order than CRN models; however, the FEM shows that the order decreases with annealing [14] whereas here we clearly observe an increase.…”
Section: Articlementioning
confidence: 44%
“…Paracrystalline models do indeed depict more dihedral order than CRN models; however, the FEM shows that the order decreases with annealing [14] whereas here we clearly observe an increase.…”
Section: Articlementioning
confidence: 44%
“…[11][12][13] An early high-pressure ͑diamond anvil͒ study on vacuum-evaporated a-Si reported a transformation to a metallic phase that was consistent with high density amorphous Si. We believe that the mechanical behavior can be explained by well documented structural differences [19][20][21][22] between highly defective or paracrystalline unrelaxed a-Si and the fully fourfold coordination of relaxed a-Si which has only short range order and is a continuous random network ͑CRN͒. A further study based on diamond anvil results has also proposed that a-Si should undergo a transformation to a high density ͑metallic͒ amorphous phase during loading and transform back to its original low density a-Si state during unloading.…”
Section: Introductionmentioning
confidence: 94%
“…If the structure changes dramatically during image acquisition, we will not be able to reproduce the results. In previous work [5,9], as-prepared and near-surface amorphous silicon is found to be paracrystalline. Is this paracrystalline structure beam-sensitive and how will it change with electron energy?…”
Section: Methodsmentioning
confidence: 90%
“…Indeed, this prediction is confirmed by our experiments, which were done separately in the JEOL 4000 and Philips CM12 microscopes (we ever attempted to use one microscope to do both hollow cone and dark field, but did not succeed). The operating conditions for these microscopes can be found elsewhere [5,6].…”
Section: Introductionmentioning
confidence: 99%